Management of the dialysis patient for the hospital physician. Issue 1005 (5th July 2009) - Power, A; Duncan, N; Goodlad, C
Abstract : As a relative shortage of organs limits transplantation rates in many countries, the number of patients on dialysis is increasing. Nephrologists in specialist centres supervise their dialysis, but increasingly in the context of acute medical emergencies, such patients present to district general hospitals. Experience in managing patients on dialysis varies among institutions. This review aims to provide a practical guide to aid general physicians involved in the delivery of hospital care, by outlining the principles of dialysis (haemodialysis and peritoneal dialysis) and examining relevant medical issues specific to dialysis patients.